Impact of the tropical cyclone Nilam on the vertical distribution of carbon monoxide over Chennai on the Indian peninsula. (21st September 2018) - Sahu, Lokesh K.; Tripathi, Nidhi; Sheel, Varun; Kajino, Mizuo; Deushi, Makoto; Yadav, Ravi; Nedelec, Philippe
Abstract : The present study investigates the impact of tropical cyclone (TC) Nilam on the vertical distribution of carbon monoxide (CO) over Chennai in southern India. Measurements of OZone and water vapour by Airbus In‐service airCraft (MOZAIC) profiles of CO measured during October–November 2012 were analysed. The vertical profiles of CO on 15 October and 2 November were influenced by convective motions with a significant decrease in outgoing long‐wave radiation (OLR) compared to that on normal days of observations. The near‐surface mixing ratios of CO (185 ± 24 ppbv) in convectively influenced conditions were much lower than those measured during normal days (>210 ppbv). The occurrence of minimum CO values at altitudes of 4–6 km coincided with the lowest lapse rate (LR) value of 4–5 °C/km. The uplift of surface air masses led to a large increase in the CO mixing ratio in the free troposphere. The differences in CO between the lower and free troposphere were relatively small (40–50 ppbv) and large (90–100 ppbv) during convective and normal days, respectively. In the lower troposphere, elevated values of CO (>250 ppbv) were measured for lighter wind speeds from the north, while lower values (<150 ppbv) were measured for strong winds from the western sectors. The Model for OZone And Related chemical Tracers (MOZART‐4) and Chemistry Climate Model 2 (CCM2) simulations did not capture the detailed features of the CO profiles. For cyclone‐influenced measurements in the lower troposphere, MOZART‐4 underestimated the CO values by approximately 13%, but CCM2 overestimated the CO values by 70%. In the upper troposphere, MOZART‐4 and CCM2 underestimated the observations by 6–8% and 12–22%, respectively. The mixing scheme of the model and simulated concentrations seem to be the key causes of disagreements. However, the performances of both the MOZART‐4 and CCM2 simulations were better for convection‐free normal days. Abstract : Comparison of mean values of CO (MOZAIC observation) in the PBL (0–3 km) and free troposphere (3–12 km) for different days of study period over Chennai in post‐monsoon season. The differences of CO between PBL and free troposphere on convective days were about two times lower than those observed during normal days. Convective dynamics in post‐monsoon season over peninsular India lead to efficient vertical mixing and redistributions of trace gases.